THE CORRELATION BETWEEN EFL LEARNERS’ SPEAKING COMPETENCY AND THE USE OF PODCASTS - HERNING BUDIASTONO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2021)
Speaking is one of the important parts of communication. Every EFL learners have to master this skill. Use podcasts in improving their speaking skills is one method that helps them to learn it in an easy way. This study explored that podcast gave a contribution toward the speaking competency of vocational high school students. The finding showed that the correlation of podcasts as the independent variable (X) and speaking as the dependent variable was positive. It indicated that podcast has a positive contribution to EFL learners’ speaking competency.